Oriented on security enterprises operating environment – subjects of foreign economic activity (Economics and region, 2018)
The problems on security oriented environment of domestic enterprises - subjects of external economic activity functioning formation have been worked out. The necessity of taking into account the market participant behavior modification according to the specific external (institutional) and internal (adaptive) environments has been grounded. The formation peculiarities of domestic companies environment functioning (domestic business environment, macroenvironment, microenvironment) from the perspective of influence on economic security have been highlighted. It has been determined that the domestic business environment creates a common business «background» within a country and affects all companies regardless of domain and activity peculiarities. It is being transformed thus changing the vector of domestic business in the global economy. It has been mentioned that from the perspective of economic security of a domestic market participant those macroenvironment factors that could potentially affect a determined enterprise in view of the activity sphere and interactions peculiarities with foreign markets are to be taken into consideration. It has been proved that the enterprise microenvironment and internal environment can be influenced by processes of «economic diffusion», i. e. a certain levelling limits of a determined market participant functioning. This is due to the innovative marketing approaches intensification in order to engage potential customers in the production process, as well as establishing a qualitatively new interaction even with competitors (different levels of competition / cooperation for different markets). The environment model of external economic activity subjects functioning in the context of economic security has been stipulated.
Keywords: economic security; functioning environment; external economic activity